Comprehensive Investigation into the Thermal Performance of Nanofluid-Enhanced Heat Pipes for Advanced Thermal Management Systems - Mohan Govindasamy; Manikandan Ezhumalai; Ratchagaraja Dhairiyasamy; Deekshant Varshney; Subhav Singh; Deepika Gabiriel (Eng)
This study investigates the thermal performance of heat pipes using nanofluids based on silver (Ag), aluminum oxide (Al2O3), and multi-walled carbon nanotubes (MWCNTs) at varying concentrations. Heat pipes, recognized for their efficiency in passive thermal management, face limitations with traditional fluids. Nanofluids, engineered by dispersing nanoparticles in base fluids, were explored as alternatives due to their superior thermal conductivity and convective properties. Nanofluids were prepared using ultrasonication, and their thermal conductivity, viscosity, and stability were evaluated. Experimental tests were conducted under controlled conditions to assess the impact of nanoparticle type, concentration, inclination angle, and fluid filling ratio on performance metrics, including thermal resistance (TR) and heat transfer coefficients (HTCs). The results demonstrated that Ag-based nanofluids outperformed others, achieving a 150% increase in thermal conductivity and an 83% reduction in TR compared to deionized water. HTCs increased by 300% for Ag nanofluids at a 0.5% concentration. Inclination angles and filling ratios also significantly affected performance, with optimal conditions identified at a 70% filling ratio and a 30° inclination angle. The findings highlight the potential of nanofluids in optimizing heat transfer systems and provide a framework for selecting suitable parameters in industrial applications.